International functions of sport (based on the example of bilateral relations between Russia and the Baltic States) - Letko, Paweł (Przegląd Wschodnioeuropejski, 2023)
The topic of this article is the function of sport in Russia’s bilateral relations with the Baltic States. The author attempts to define the goals which the Russian Federation wants to accomplish by using sport as a ‘soft power’ in relations with the Baltic States. The concept of the article is based on an analysis of three forms of sport politicisation described in the subject literature – as a collector (a carrier of certain values or ideas), a catalyst (a factor initiating processes or events) and a facilitator (the means facilitating communication and understanding). The examples provided as an illustration of the theses relate to the events that took place from 2002 to 2018. The source material consists predominantly of information obtained from online information portals, such as Delfi, RIA, Nowosti and Postimees. The analysis has showed that, in its relations with the Baltic States, Russia tries to use sport to strengthen its position and improve its image internationally. It also attempts to implement a historical policy at sporting events as well as use sporting rivalry as a demonstration of its power.